LED light sources and their tract on the supply network - Baran, Aliaksandr N.; Pashinski, Vasiliy A.; Lipnizki, Leonid A. (Journal of the Belarusian State University. Ecology, 2020)
The results of studies of the operation of LED strips and spotlights, which are a non-linear load with harmonic components, are analyzed. High harmonics arising from the use of LED light sources lead to a significant increase in losses during energy transfer, a decrease in power factor, and can cause malfunctions of the start-up protection equipment. When choosing start-up devices for supply lines, it is necessary to introduce corrective coefficients that take into account the nonlinear nature of LED technology. Replacement of incandescent lamps and gas-discharge light sources in the Republic of Belarus will reduce the technogenic load on the ecosystem in the production of electricity.